Early Creeping Attachment Noted after Mandibular Labial Frenuloplasty - P. Stylianou; N. Soldatos; E. K. Edmondson; N. Angelov; R. Weltman (Hindawi Limited, 2020)
Recession of the mandibular central incisors is frequently associated with high frenum insertion. Often times, this recession is accompanied by a lack of sufficient amount of keratinized tissue and absence of attached gingiva. In this case report, an ASA I patient presented with Cairo Recession Type 2 (RT2) and a minimal amount of keratinized tissue on the mandibular central incisors and underwent frenuloplasty in the anterior mandible with the use of a conventional scalpel technique due to high frenum attachment. The results demonstrated creeping attachment of 1.0 mm as early as 10 days postoperatively resulting in complete root coverage and closure of the interproximal space between teeth #24 and 25. A second soft tissue surgery was avoided due to complete root coverage which remained stable at the 6-month follow-up appointment.